The study of indoor air quality at lecture classroom, University Malaysia Pahang - Ain Nadia Nadira, Marafi (2017)
The study had been done on the air quality measurement at Universiti Malaysia Pahang. The study was conducted at different place which is inside the lecture classrooms and outside the lecture classrooms. This study was conducted for 12 hours per day starting from 8.00 am until 8.00 pm. The measurement of air quality was taken 3 times for each study areas. In this study, the level of concentration of sulfur dioxide (SO 2), nitrogen dioxide (NO2) and particulate matter (PM10) was measured. The average SO2 reading inside lecture classroom at UMP Gambang and UMP Pekan is 0.00 ppm. For the reading of SO 2 outside lecture classroom, the average concentration reading recorded for UMP Gambang is 0.074 ppm and for UMP Pekan is 0.053 ppm. The average concentration of NO2 reading inside lecture classroom at TJMP Gambang is 0.015 ppm and for UMP Pekan the average reading is 0.010 ppm. For the reading of NO2 outside lecture classroom, the value recorded is 0.00 ppm. For the PM10 reading, the average reading inside lecture classroom is 20 μg/m3 for UMP Gambang, follow by UMP Pekan which the reading is 18 μg/m3 . For outside lecture classroom, the average reading for PM 10 is 68 μg/m3 which is at UMP Gambang follow by UMP Pekan which the reading is 20 μg/m3.